Psychotherapy in Jordan: An Investigation of the Host and Syrian Refugee Community’s Perspectives - Karnouk, Carine; Böge, Kerem; Hahn, Eric; Strasser, Judith; Schweininger, Stephanie; Bajbouj, Malek (Frontiers in Psychiatry, 2019)
Little is known about patient satisfaction, bias, stigma, and the effects of psychotherapy within the Kingdom of Jordan or the Arab world in general. The purpose of this study was to explore the perceptions of both the Jordanian host and refugee community members from the psychotherapeutic services offered at various mental health care settings in Jordan. A sample of 100 patients who received psychosocial expert interventions was recruited between October and December 2017 in Amman, Jordan. Participants were either from the host or Syrian refugee community or contacted through multiple organizations working in the mental health field. The Patient Satisfaction Questionnaire, which consists of four subscales covering 1) patient satisfaction, 2) bias toward therapy, 3) effects of therapy, and 4) stigma, was administered. As a means of investigation and exploration, descriptive statistics of participant responses are displayed. Results revealed overall high rates of satisfaction with provided services and perceived benefits of psychotherapeutic interventions. However, respondents showed ambivalence regarding bias and stigma. Subsample analyses indicated no significant differences between both communities. These findings give an understanding of perceptions surrounding psychotherapy in Jordan and some insights on therapeutic processes that may be useful for clinical applications and future research.